Evaluation on the basis biochemical parameters effect of hospital high protein diet on the health of patients with subarachnoid hemorrhage. - Marta Diana Komarowska; Izabela Janowicz; Anna Krysińska; Adam Hermanowicz; Jan Kochanowicz (Kazimierz Wielki University, 2016)
The studies show influence of protein-rich hospital diet on health condition of the patient with subarachnoid hemorrhage treated at the Department of Neurosurgery in Medical University in Bialystok. The analysis was made retrospectively. We obtain all data from the day of the admission and discharge day. The data included demographic data, blood count, glucose level, electrolytes and blood protein level. We also analyzed the hospital protein rich average menu since ten years.